A mediating model of resource commitment, reverse logistics and financial performance: importance-performance map analysis - Fernando, Yudi; Muhammad Shabir, Shaharudin; Ishak, Ismail; Yew, Shu Qi; Yuvaraj, Ganesan (Universiti Malaysia Sarawak (UNIMAS), 2018)
The aim of this paper is to examine a mediating model of resource commitment, reverse logistics and financial performance. In addition, this paper presents the importance-performance map analysis (IMPA) to examine the critical domains of resource commitment and reverse logistics on financial performance. This study conducted a survey among 113 manufacturing companies including first tier and second tier suppliers in automotive industry. The results of the study indicated that important of resource commitment makes reverse logistics program more effective and efficient. The results provide empirical evidence of the mediating impact of reverse logistics on the relationship between resource commitment and financial performance. As the evidence show in this study, the finding has opened new research and development opportunities to identify new alternatives income source to a company and generate benefits from resource commitment in reverse logistic activities while comply with environmental standard.